1976
DOI: 10.1111/j.1532-5415.1976.tb06781.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Systems for Stroke Rehabilitation in a General Hospital

Abstract: This study was designed to compare the effectiveness of stroke rehabilitation therapy in a specialized Stroke Unit with that provided on the medical service of a general hospital (Rhode Island Hospital). The 8-bed Stroke Unit is staffed by a multidisciplinary team, and a weekly conference is held for evaluation and planning. On the basis of data obtained from the hospital records, two groups of patients were studied: 224 who were treated in the Stroke Unit, and 110 who were evaluated and approved for admission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 4 publications
(6 reference statements)
0
17
0
Order By: Relevance
“…8 Several groups have conducted controlled trials comparing the outcome of patients from stroke units with those from medical wards. The first such study 9 reported no benefit for mildly and severely affected patients but a significantly better outcome for patients with moderate disabilities. Feigenson and colleagues 10 showed in a similar trial that patients admitted to a stroke unit were more likely to be discharged home and were able to walk better.…”
Section: Evidence Concerning the Effectiveness Of Rehabilitationmentioning
confidence: 99%
“…8 Several groups have conducted controlled trials comparing the outcome of patients from stroke units with those from medical wards. The first such study 9 reported no benefit for mildly and severely affected patients but a significantly better outcome for patients with moderate disabilities. Feigenson and colleagues 10 showed in a similar trial that patients admitted to a stroke unit were more likely to be discharged home and were able to walk better.…”
Section: Evidence Concerning the Effectiveness Of Rehabilitationmentioning
confidence: 99%
“…8 Another definition which has been suggested is "a geographic location within the hospital designated for stroke and stroke-like patients who are in need of rehabilitation services and the skilled professional care that such a unit can provide." 9 A major advantage which has been put forward for having a special unit is the opportunity of developing a collaborative policy for stroke rehabilitation. 10 Such a policy should include a comprehensive assessment of all aspects of patients' illness and disability, close collaboration between the different disciplines involved, identification and awareness of objectives of rehabilitation and an educational role.…”
Section: Conceptmentioning
confidence: 99%
“…Comparative studies evaluating the effects of these units have, with one exception, 7 determined that patients achieved better functional outcomes. 8 " 10 Patients cared for in these units were sometimes, 8 but not always, 9 " more frequently discharged to home. In-hospital mortality, 7 "" and length of stay" were not positively influenced, but the units appeared to be effective in promoting family participation in patient care and the rehabilitation process.…”
mentioning
confidence: 99%
“…Both studies 9 l0 compared care provided by a multidisciplinary team in specialized stroke units with care delivered on general medical wards. The Garraway study 10 only admitted patients who had a good prognosis for survival but who were unlikely to achieve independence without remediation.…”
mentioning
confidence: 99%
See 1 more Smart Citation